Preparation process and product of high-gloss wear-resistant water-based plastic transfer aluminum plating paper
Patent Information
- Application Number
- CN202611337091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]为了解决现有的镀铝纸环保性较低,且在后工序的UV印刷中,容易出现UV印刷层与镀铝纸的PET薄膜层结合性较低,使得UV印刷层容易出现毛边,长期使用容易出现磨损和脱落的问题,本申请提供一种高光泽耐磨的水性替塑转移镀铝纸的制备工艺及产品
本申请的一种高光泽耐磨的水性替塑转移镀铝纸的制备工艺,通过先在基膜层上制备可剥离的镀铝涂层,再将镀铝涂层转移贴合至纸张层,最后撕离基膜,从而完全替代了传统PET镀铝纸中的难以回收的PET薄膜层,显著提升了镀铝纸的环保性。镀铝涂层作为应用的表面层,能够与后工序中的UV印刷层稳定结合。
Smart Images

Figure CN122960052A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of metallized paper, and in particular to a preparation process and product of a high-gloss, wear-resistant, water-based plastic-substitute transfer metallized paper. Background Technology
[0002] Metallized paper is a packaging material with an aluminum coating effect. It has good light-blocking and UV protection effects, which not only extends the shelf life of packaged goods, but also improves the appearance and texture of packaged goods. To a certain extent, it has replaced aluminum foil and is widely used in electronic product packaging, wine packaging, paper bags, cosmetic packaging, clothing tags, or game cards.
[0003] Existing metallized paper typically consists of a PET film layer, a vacuum metallized layer, a base coating layer, an EVA hot melt adhesive layer, and a paper layer, laminated sequentially. The preparation method generally involves: forming a vacuum metallized layer on the surface of the PET film layer using vacuum metallization; then applying a base coating layer to the surface of the vacuum metallized layer; and finally laminating the paper layer using the EVA hot melt adhesive layer. Protected by the PET film layer, the resulting metallized paper exhibits good waterproof, moisture-proof, scratch-resistant, and abrasion-resistant properties.
[0004] However, the aforementioned metallized paper has the following problems: First, the PET film layer has low recyclability, which reduces the environmental friendliness of the metallized paper; Second, when UV printing is performed on the surface of the PET film layer corresponding to the metallized paper in the subsequent process, the UV printing layer has low adhesion to the PET film layer of the metallized paper, which makes the UV printing layer prone to rough edges. Long-term use can easily lead to wear and peeling, reducing the application performance of the metallized paper. Summary of the Invention
[0005] To address the issues of low environmental friendliness of existing metallized paper and poor adhesion between the UV printing layer and the PET film layer of the metallized paper during subsequent UV printing processes, which leads to rough edges, wear, and peeling of the UV printing layer over long-term use, this application provides a preparation process and product for high-gloss and wear-resistant water-based plastic-substitute transfer metallized paper.
[0006] In a first aspect, this application provides a preparation process for high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper, employing the following technical solution: A process for preparing a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper, comprising the following steps: S1. Apply water-based aluminizing coating to the surface of the base film layer, and after drying and curing, form an aluminizing coating. S2. Apply hot melt adhesive to the surface of the aluminized coating, then heat press it to the paper layer, and then peel off the base film layer to obtain a high-gloss and wear-resistant water-based plastic transfer aluminized paper. The water-based aluminum coating is made from the following raw materials in parts by weight: 35-45 parts water-based acrylic resin, 20-28 parts aluminum powder, 8-12 parts reactive monomer, 2-4 parts dispersant, 0.2-0.4 parts photoinitiator, 0.05-0.2 parts antioxidant, and 50-60 parts water.
[0007] By adopting the above technical solution, the preparation process of this application first prepares a peelable aluminized coating on the base film layer, then transfers and adheres the aluminized coating to the paper layer, and finally peels off the base film, thereby completely replacing the difficult-to-recycle PET film layer in traditional PET aluminized paper and significantly improving the environmental friendliness of aluminized paper.
[0008] In this application, the aluminized paper has an aluminized coating on its outer surface. Therefore, the aluminized coating in this application is formed by drying and curing a water-based aluminized coating with specific components, which imparts excellent gloss and abrasion resistance to the aluminized paper. Simultaneously, it can stably bond with the UV printing layer in subsequent processes, thus completely solving the problems of burrs, wear, and peeling caused by poor adhesion between the traditional PET film layer and the UV printing layer. Specifically, the water-based aluminized coating uses water-based acrylic resin as the main film-forming agent, giving the aluminized coating a good gloss and abrasion resistance foundation. Aluminum powder is dispersed in the water-based acrylic resin system, giving the aluminized coating a uniform and excellent metallic aluminized texture. Simultaneously, the introduction of reactive monomers and dispersants into the water-based acrylic resin system creates a synergistic effect. Under the action of a photoinitiator, during the curing process, it further undergoes a cross-linking reaction with the water-based acrylic resin to form a cross-linked network structure. This cross-linked network structure not only has good strength and toughness but also allows the aluminum powder to be stably interwoven and dispersed, forming a tightly bonded aluminized coating. It also improves the adhesion stability of the UV printing layer in subsequent processes.
[0009] Preferably, the aluminum powder is spherical aluminum powder with a particle size of 0.5-3 micrometers.
[0010] By employing the above-mentioned technical solution, the excellent dispersibility and flowability of the micron-sized spherical structure allow it to be uniformly distributed in the water-based acrylic resin matrix, forming a smooth, dense, and highly reflective microscopic surface, thereby significantly improving the gloss of the aluminum-coated coating. Simultaneously, the moderate particle size of 0.5-3 microns ensures a smooth and delicate surface for the aluminum-coated coating, avoiding the roughness caused by excessively large particles, while also providing an effective physical barrier for the coating, synergistically enhancing its wear resistance.
[0011] Preferably, the reactive monomers consist of tris(2-hydroxyethyl) isocyanurate triacrylate, ethylene glycol dimethacrylate and β-carboxyethyl acrylate in a weight ratio of 1:(1-2):(0.3-0.5).
[0012] By employing the above technical solutions, trifunctional tris(2-hydroxyethyl)isocyanurate triacrylate can construct a three-dimensional network framework with high cross-linking density, endowing the aluminized coating with excellent hardness and abrasion resistance; difunctional ethylene glycol dimethacrylate acts as an active diluent and cross-linking bridge, adjusting the system viscosity and optimizing cross-linking uniformity; monofunctional β-carboxyethyl acrylate introduces abundant carboxyl groups, which are enriched on the surface of the aluminized coating, improving the interlayer adhesion between the aluminized paper surface and the UV printing layer, and eliminating the risk of printing burrs and UV printing layer peeling off. The three components work synergistically as reactive monomers, helping to further improve the gloss, abrasion resistance, and adhesion of the UV printing layer in subsequent processes.
[0013] Preferably, the dispersant is composed of methacryloyloxypropyl cage-type polysilsesquioxane and acrylamide-polyethylene glycol 400-hydroxy in a weight ratio of 1:(0.1-0.3).
[0014] By employing the above technical solution, methacryloyloxypropyl cage-like polysilsesquioxane possesses a nanoscale cage-like structure, which can effectively disperse aluminum powder through steric hindrance, preventing its agglomeration. Simultaneously, its own acryloyl functional groups can participate in photocuring crosslinking, anchoring the siloxane structure within the aluminized coating network, significantly improving the coating's strength and abrasion resistance. On the other hand, acrylamide-polyethylene glycol 400-hydroxyl, as a polymeric dispersant, has a long-chain structure that can efficiently disperse aluminum powder and water-based acrylic resin through steric stabilization. Its terminal hydroxyl and amide groups can enhance the polarity and wettability of the coating surface, further promoting bonding with the UV printing layer. The synergistic effect of these two components ensures uniform dispersion of the aluminum powder, ultimately improving the gloss, abrasion resistance, and printability of the aluminized paper.
[0015] Preferably, the photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-bis(p-tolyl)phosphine oxide.
[0016] By employing the above technical solution and combining two different types of photoinitiators, the efficiency of UV curing was maximized. 1-Hydroxycyclohexylphenyl ketone mainly absorbs short-wavelength UV light, efficiently initiating the polymerization of acrylate double bonds on the coating surface, ensuring rapid surface setting and achieving high gloss and surface dryness; while 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide can absorb longer-wavelength UV light, deeply initiating curing, and is especially suitable for thick coating systems containing aluminum powder, ensuring complete curing even at the bottom of the coating.
[0017] Preferably, the antioxidant is antioxidant 1010 and / or antioxidant 168.
[0018] By adopting the above technical solution, peroxide free radicals generated during the photocuring and long-term use of the coating are effectively captured and decomposed, inhibiting the oxidative degradation reaction of the polymer backbone. This not only ensures the chemical stability of the water-based aluminized coating during preparation, storage, and curing, avoiding yellowing and performance degradation caused by thermal or photo-oxidation, but also endows the final product with excellent aging resistance, enabling it to maintain high gloss, high adhesion, and long-term stability of overall appearance even under long-term light exposure or humid and hot environments.
[0019] Preferably, the dry film thickness of the aluminum coating is 28-32 μm.
[0020] By adopting the above technical solution, the optimal thickness can ensure that the aluminum powder is fully spread to provide excellent gloss and covering effect, while also giving the coating sufficient strength to resist scratches and maintaining good flexibility to adapt to the bending and deformation of the paper.
[0021] Preferably, the drying temperature in step S1 is 70-90℃, and the drying time is 2-5 min; the curing is UV curing, and the curing time is 10-15 s.
[0022] By adopting the above technical solution, baking at a medium temperature of 70-90℃ for 2-5 minutes can gently and thoroughly remove moisture from the coating, avoiding blistering or cracking caused by high temperatures, and providing a completely dry, moisture-free solid film for subsequent UV curing. Subsequently, UV curing for 10-15 seconds is performed. This rapid curing process not only significantly improves production efficiency but also ensures that the coating rapidly cross-links in a completely dry state, forming a dense network with high hardness, high gloss, and tight bonding with the aluminum powder.
[0023] Preferably, the surface dyn value of the dried aluminized coating is ≥36 dyn / cm.
[0024] By adopting the above technical solution, a good wetting surface can be achieved without additional corona treatment, allowing for full wetting and spreading of UV inks. This directly solves the fundamental defect of poor wetting properties of PET films in existing technologies, enabling the UV printing layer in subsequent processes to form a tight contact with the aluminized coating. This fundamentally avoids the generation of printing burrs and significantly improves the wear resistance and peeling resistance of the UV printing layer under long-term use, ensuring the fineness and durability of the final printed product.
[0025] Secondly, this application provides a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper, employing the following technical solution: A high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper is prepared by the above-mentioned preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper.
[0026] By adopting the above technical solution, the resulting high-gloss, wear-resistant water-based plastic-altering transfer metallized paper completely eliminates the difficult-to-recycle PET film layer in its product structure, resulting in excellent environmental performance. Simultaneously, its surface metallized coating possesses high gloss, strong wear resistance, and high surface energy, exhibiting excellent adhesion to the subsequent UV printing layer.
[0027] In summary, this application includes at least one of the following beneficial technical effects: This application discloses a process for preparing a high-gloss, wear-resistant, water-based plastic-alternative transfer metallized paper. This process involves first preparing a peelable metallized coating on a base film layer, then transferring and bonding the metallized coating to the paper layer, and finally peeling off the base film. This completely replaces the difficult-to-recycle PET film layer in traditional PET metallized paper, significantly improving the environmental friendliness of the metallized paper. The metallized coating, as the surface layer for application, can stably bond with the UV printing layer in subsequent processes.
[0028] By further using a water-based aluminizing coating made from water-based acrylic resin, aluminum powder, a reaction monomer composed of tri(2-hydroxyethyl)isocyanurate, ethylene glycol dimethacrylate and β-carboxyethyl acrylate, a dispersant composed of methacryloyloxypropyl cage-type polysilsesquioxane and acrylamide-polyethylene glycol 400-hydroxyl, a photoinitiator, an antioxidant and water, an aluminizing coating is formed after drying and curing. This coating can give the aluminized paper excellent gloss, abrasion resistance and surface wettability. At the same time, it can stably bond with the UV printing layer in the subsequent process, thus completely solving the problems of burrs, wear and peeling caused by poor adhesion between the traditional PET film layer and the UV printing layer. Attached Figure Description
[0029] Figure 1 This is a physical image of a high-gloss, wear-resistant, water-based plastic-substitute transfer metallized paper according to this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the embodiments.
[0031] The following are some of the sources and specifications of the raw materials used in this application. The raw materials used in the preparation examples and embodiments of this application can all be obtained commercially, including but not limited to the following models and manufacturers of raw materials. Raw materials with equivalent performance can also be used: Water-based acrylic resin: Seacryl 11K40, a new material from Seacryl. Tris(2-hydroxyethyl)isocyanurate triacrylate: Lankel L-61034; Acrylamide-PEG400-OH, Ruixi Biotechnology ; Base film layer: BOPP film or PET release film, thickness 12-20 micrometers, release force 8-10g / in; Hot melt adhesive: EVA hot melt adhesive, commercially available, Guangdong Kaisheng New Materials; Paper layer: white cardboard, thickness 0.2-1mm, weight 200-400g / m²; Preparation example of water-based aluminized coating Preparation Example 1 Preparation Example 1 discloses a water-based aluminum plating coating, which is prepared by the following steps: 3.5 kg of waterborne acrylic resin, 0.8 kg of reactive monomer, 0.4 kg of dispersant, and 0.005 kg of antioxidant were added to 5 kg of water and stirred evenly. Then, 2 kg of aluminum powder was added and stirred evenly, followed by 0.02 kg of photoinitiator and stirred evenly to obtain a waterborne aluminum coating. The reactive monomer consisted of trimethylolpropane triacrylate and ethylene glycol dimethacrylate in a weight ratio of 1:1. The dispersant consisted of methacryloyloxypropyl cage-type polysilsesquioxane and polyethylene glycol 400. The aluminum powder was spherical with a particle size of 0.5-1 micrometer. The photoinitiator consisted of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide in a weight ratio of 1:1. The antioxidant consisted of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.
[0032] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 lies in the different preparation process parameters, as detailed below: 4 kg of waterborne acrylic resin, 1 kg of reactive monomer, 0.3 kg of dispersant, and 0.012 kg of antioxidant were added to 5.5 kg of water and stirred until homogeneous. Then, 2.4 kg of aluminum powder was added and stirred until homogeneous, followed by 0.03 kg of photoinitiator and stirred until homogeneous to obtain a waterborne aluminum coating. The reactive monomer consisted of tri(2-hydroxyethyl)isocyanurate triacrylate and ethylene glycol dimethacrylate in a weight ratio of 3:1. The dispersant consisted of vinyltrimethoxysilane and polyethylene glycol 400. The aluminum powder was spherical with a particle size of 1-2 micrometers. The photoinitiator consisted of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide in a weight ratio of 1:2. The antioxidant consisted of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:2.
[0033] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 lies in the different preparation process parameters, as detailed below: 4.5 kg of waterborne acrylic resin, 1.2 kg of reactive monomer, 0.2 kg of dispersant, and 0.02 kg of antioxidant were added to 6 kg of water and stirred until homogeneous. Then, 2.8 kg of aluminum powder was added and stirred until homogeneous, followed by 0.04 kg of photoinitiator and stirred until homogeneous to obtain a waterborne aluminum coating. The reactive monomer consisted of tri(2-hydroxyethyl)isocyanurate triacrylate and methyl methacrylate in a weight ratio of 1:1. The dispersant was methacryloyloxypropyl cage-type polysilsesquioxane. The aluminum powder was spherical aluminum powder with a particle size of 2-3 micrometers. The photoinitiator consisted of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide in a weight ratio of 1:0.5. The antioxidant consisted of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3.
[0034] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the reaction monomers consist of tris(2-hydroxyethyl)isocyanurate triacrylate, ethylene glycol dimethacrylate and β-carboxyethyl acrylate in a weight ratio of 1:1:0.5, while the rest is the same as Preparation Example 1.
[0035] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the reaction monomers consist of tris(2-hydroxyethyl)isocyanurate triacrylate, ethylene glycol dimethacrylate and β-carboxyethyl acrylate in a weight ratio of 1:2:0.3, while the rest is the same as Preparation Example 1.
[0036] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the dispersant is composed of methacryloyloxypropyl cage-type polysilsesquioxane and acrylamide-polyethylene glycol 400-hydroxy in a weight ratio of 1:0.1, while the rest is the same as Preparation Example 4.
[0037] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that the dispersant is composed of methacryloyloxypropyl cage-type polysilsesquioxane and acrylamide-polyethylene glycol 400-hydroxy in a weight ratio of 1:0.3, while the rest is the same as Preparation Example 4.
[0038] Example Example 1
[0039] Example 1 discloses a preparation process for a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper, comprising the following steps: S1. The water-based aluminum coating prepared in Preparation Example 1 was coated on the surface of a BOPP base film with a thickness of 12 micrometers. After drying and curing, an aluminum coating was formed. The drying temperature was 70℃ and the drying time was 5 min. The curing was carried out by 395nm ultraviolet light curing for 10 s. The dry film thickness of the aluminum coating was 32 μm and the surface dyn value was ≥36 dyn / cm. S2. Apply a 10-micron thick hot melt adhesive to the surface of the aluminized coating, and then heat-press it with a 0.2mm thick, 200g / m² white cardboard as the paper layer. The heat-pressing temperature is 110℃, the pressure is 3MPa, and the time is 3min. Then peel off the base film layer to obtain a high-gloss and wear-resistant water-based plastic transfer aluminized paper.
[0040] Example 2
[0041] The difference between Example 2 and Example 1 lies in the different process parameters, as detailed below: S1. The water-based aluminized coating obtained in Preparation Example 2 was coated on the surface of a PET base film layer with a thickness of 20 micrometers. After drying and curing, an aluminized coating was formed. The drying temperature was 80℃ and the drying time was 2 min. The curing was carried out by 395nm ultraviolet light curing and the curing time was 15 s. The dry film thickness of the aluminized coating was 30 μm and the surface dyn value was ≥36 dyn / cm. S2. Apply a 12-micron thick hot melt adhesive to the surface of the aluminized coating, and then heat-press it with a 0.5mm thick, 270g / m² white cardboard as the paper layer. The heat-pressing temperature is 115℃, the pressure is 4MPa, and the time is 2.5min. Then peel off the base film layer to obtain a high-gloss and wear-resistant water-based plastic transfer aluminized paper.
[0042] Example 3
[0043] The difference between Example 3 and Example 1 lies in the different process parameters, as detailed below: S1. The water-based aluminum coating obtained in Preparation Example 3 was coated on the surface of a BOPP base film with a thickness of 15 micrometers. After drying and curing, an aluminum coating was formed. The drying temperature was 75℃ and the drying time was 4 min. The curing was carried out by 395nm ultraviolet light curing and the curing time was 12 s. The dry film thickness of the aluminum coating was 28 μm and the surface dyn value was ≥36 dyn / cm. S2. Apply a hot melt adhesive with a thickness of 8 micrometers to the surface of the aluminized coating, and then hot-press it with a 0.8mm thick, 320g / m² white cardboard as the paper layer. The hot-pressing temperature is 120℃, the pressure is 5MPa, and the time is 2min. Then peel off the base film layer to obtain a high-gloss and wear-resistant water-based plastic transfer aluminized paper.
[0044] Example 4
[0045] The difference between Example 4 and Example 1 is that the water-based aluminum coating is derived from Example 4, while the rest is the same as Example 1.
[0046] Example 5
[0047] The difference between Example 5 and Example 1 is that the water-based aluminum coating is derived from Example 5, while the rest is the same as Example 1.
[0048] Example 6
[0049] The difference between Example 6 and Example 4 is that the water-based aluminum coating is derived from Example 6, while the rest is the same as Example 4.
[0050] Example 7
[0051] The difference between Example 7 and Example 4 is that the water-based aluminum coating is derived from Example 7, while the rest is the same as Example 4.
[0052] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S1, a 5-micron thick aluminum coating is formed on the surface of the corona-treated PET film using vacuum aluminum plating, and in step S2, the PET film is not peeled off. Otherwise, it is the same as Example 1.
[0053] Performance testing The following tests were conducted on the performance of the metallized paper prepared in Examples 1-7 and Comparative Example 1: Gloss test Gloss (unit: GU) was measured using a gloss meter at a 60° test angle. Abrasion resistance test Using an abrasion tester with a load of 500g, friction medium of 80g / m² offset paper, and a friction rate of 60 times / min, the test measures the number of abrasion resistance tests conducted when the aluminized coating of the aluminized paper shows signs of wear (unit: times). UV printing test 1) Using an ink printer, print text on the surface of aluminized paper (printing ink is Guangyi Matsui ink, model 1710). After baking at 75℃ for 2 minutes, cure with 395nm ultraviolet light. After curing, observe whether there are any rough edges on the UV printed layer. Use 3M 810 tape for adhesion testing. The adhesion test uses the cross-cut adhesion test method. The adhesion grades are 5B, 4B, 3B, 2B, 1B and 0B in that order. Among them, 5B is the best and 0B is the worst. Record the test results. 2) Using an ink printing machine, text was printed on the surface of aluminized paper (printing ink was Guangyi Matsui ink, model 1710). After baking at 75℃ for 2 minutes, it was cured with 395nm ultraviolet light. The UV-printed aluminized paper was sealed and placed in a constant temperature and humidity chamber at 85℃ and 85% humidity for 7 days. Adhesion was tested using 3M 810 tape. The adhesion test used the cross-cut adhesion test method. The adhesion grades were 5B, 4B, 3B, 2B, 1B and 0B, with 5B being the best and 0B being the worst. The test results were recorded.
[0054] The following are the performance test data of the aluminized paper prepared in Examples 1-7 and Comparative Example 1. Please refer to Table 1 below for details.
[0055] Table 1 Performance data of the metallized paper prepared in Examples 1-7 and Comparative Example 1
[0056] Based on Examples 1-3 and Comparative Example 1, it can be concluded that the preparation process of this application, compared with Prior Art Document 1, not only solves the environmental protection issue but also improves the adhesion stability of the UV printing layer in the subsequent UV printing process.
[0057] Combining Examples 1-3 and Examples 4-7, it can be concluded that Examples 4-5, compared to Example 1, optimized the type and ratio of reactive monomers, resulting in improved gloss and abrasion resistance of the metallized paper. This leads to improved adhesion stability of the UV-printed layer after subsequent UV printing, with no burrs. Examples 6-7, compared to Example 4, further optimized the type and ratio of dispersant, further enhancing the gloss and abrasion resistance of the metallized paper. This also leads to improved adhesion stability of the UV-printed layer after subsequent UV printing, with no burrs. Further verification demonstrates the synergistic effect of reactive monomers and dispersants in the water-based metallized coating of this application. The metallized coating formed by the water-based metallized coating prepared using the specific components of this application exhibits good gloss and abrasion resistance. After subsequent UV printing, it can significantly improve the adhesion stability between the UV-printed layer and the metallized paper, reducing the likelihood of burrs, wear, or peeling.
[0058] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A preparation process for a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper, characterized in that, Includes the following steps: S1. Apply water-based aluminizing coating to the surface of the base film layer, and after drying and curing, form an aluminizing coating. S2. Apply hot melt adhesive to the surface of the aluminized coating, then heat press it to the paper layer, and then peel off the base film layer to obtain a high-gloss and wear-resistant water-based plastic transfer aluminized paper. The water-based aluminum coating is made from the following raw materials in parts by weight: 35-45 parts water-based acrylic resin, 20-28 parts aluminum powder, 8-12 parts reactive monomer, 2-4 parts dispersant, 0.2-0.4 parts photoinitiator, 0.05-0.2 parts antioxidant, and 50-60 parts water.
2. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The aluminum powder is spherical with a particle size of 0.5-3 micrometers.
3. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The reactive monomers consist of tris(2-hydroxyethyl) isocyanurate triacrylate, ethylene glycol dimethacrylate and β-carboxyethyl acrylate in a weight ratio of 1:(1-2):(0.3-0.5).
4. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The dispersant is composed of methacryloyloxypropyl cage-type polysilsesquioxane and acrylamide-polyethylene glycol 400-hydroxy in a weight ratio of 1:(0.1-0.3).
5. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide.
6. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The antioxidant is antioxidant 1010 and / or antioxidant 168.
7. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The dry film thickness of the aluminum coating is 28-32 μm.
8. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The drying temperature in step S1 is 70-90℃, and the drying time is 2-5 minutes; the curing is done by ultraviolet light curing, and the curing time is 10-15 seconds.
9. The preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper according to claim 1, characterized in that, The surface dyn value of the dried aluminized coating is ≥36 dyn / cm.
10. A high-gloss, wear-resistant, water-based plastic-substitute transfer metallized paper, characterized in that, It is prepared by the preparation process of a high-gloss, wear-resistant water-based plastic-substitute transfer metallized paper as described in any one of claims 1-9.